Impacts of climate change on crop production and farmers’ adaptation strategy in semi-arid zone of North-eastern Nigeria - Mohammed Bose, Mahmud (2014)
Climate change and its projected impact on the environment and socio economic systems now constitute the most important environmental problem that faces the North-eastern Nigeria which has been classified as a draught prone zone of the country. As such, it becomes imperative to assess the trend of the climatic variability, as well as its effects on crop production and farmers’ adaptation strategies in coping with the changing climate. Data applied in this study were collected from the relevant agencies of the Nigerian government, and a farm level survey data collected in 2012/2013 farming year in the North-eastern Nigeria. The climatic variability was evaluated using mean monthly temperature and rainfall data for the period 1971 – 2010 collected from Nigeria Meteorological Agency. The dataset was aggregated to obtain average yearly values and Mann Kendall test was carried out using XLSTAT software and MAKESENS Microsoft template to calculate the statistical significance of the tendencies at monthly and annual scale. The findings revealed increase in annual temperature of +0.76 °C from 1971 to 2010 has been recorded in the entire North-eastern Nigeria, whereas annual rainfall has not exhibited any significant trend. In addition, the study detected the impact of climatic variability; changes in temperature, rainfall and relative humidity on the yield of four most commonly harvested crops in the area using Crop time series model. Consistent with the global scenario, it revealed that temperature changes were found to have a discernible negative impact on the yield of all the four crops. However, rainfall and relative humidity were found to have a positive impact on the yield of all the four crops i.e. Sorghum, Millet, Maize and Cowpea. Conclusively, the adaptation strategies used by farmers to cope with the climate change and its associated constraints was identified based on a surveyed data of 400 respondents. Farmers have adopted a variety of adaptation strategies including soil conservation, change in planting date, producing agro forestry product, use of improve crop seedlings, application of mix-cropping, moving to a different site and irrigation practices in other to cope with the changing climate. Also, farmers outlined are the most important barriers to adaptation as a lack of agricultural technology, shortage of farm labour, knowledge on appropriate adaptation strategies, and government support. Lastly, a Multivariate Probit Model was used to analyse the determinants of farmer’s choices of climate change adaptation strategies and there constraints. The results from the Multivariate model highlight that household characteristics such as education, farming experience, household size, farm ownership and size, information on climate change, access to extension services, and access to credit facility are having a significant impact on adaptation to climate change. Thus, the findings provide policy recommendations and action plans to cope with the changing nature of climate change factors.